A silent gigantic solitary fibrous tumor of the pleura: case report - Gummert Jan; Niedermeyer Jost; Hansky Bert; Furukawa Nobuyuki; Renner Andre (Journal of Cardiothoracic Surgery, 2011)
Abstract Solitary fibrous tumor of the pleura is a rare mesenchymal tumor, representing less than 5% of all neoplasms associated with the pleura. A 57-year-old man had general malaise without chest symptoms for 1 month. A chest roentgenogram and computed tomography showed a giant mass in the left thorax. Although the tumor compressed the descending aorta and other mediastinal structures strongly, thereby shifting them to the right side, the patient had no symptoms except malaise. The tumor was successfully resected via two separate thoracotomies. The tumor was measured (20 cm × 19 cm × 15 cm) and weighed (2150 g). The tumor was histologically and immunohistochemically diagnosed as benign. Although SFT is benign, a long follow-up period is essential as even patients with complete resection are at risk of recurrence many years after surgery.